Differential Phosphorylation of the Glucocorticoid Receptor in Hippocampal Subregions Induced by Contextual Fear Conditioning Training - Ponce-Lina, Renata; Serafín, Norma; Carranza, Martha; Arámburo, Carlos; Prado-Alcalá, Roberto A.; Luna, Maricela; Quirarte, Gina L. (Frontiers in Behavioral Neuroscience, 2020)
Aversive events induce release of glucocorticoid stress hormones that facilitate long-term memory consolidation, an effect that depends on the activation of glucocorticoid receptors (GRs). GRs are distributed widely in the hippocampus. The dorsal region of the hippocampus has been related to cognitive functions and the ventral region to stress and emotion. GR acts as a transcription factor which after hormone binding becomes phosphorylated, affecting its cellular distribution and transcriptional activity. Two functionally well-described GR phosphorylation sites are serine 232 (pSer232), which enhances gene expression, and serine 246 (pSer246), having the opposite effect. Since gene expression is one of the plastic mechanisms needed for memory consolidation, we investigated if an aversive learning task would induce GR phosphorylation in the dorsal (DH) and the ventral (VH) hippocampus. We trained rats in contextual fear conditioning using different foot-shock intensities (0.0, 0.5, or 1.5 mA). One subgroup of animals trained with each intensity was sacrificed 15 min after training and blood was collected to quantify corticosterone (CORT) levels in serum. Another subgroup was sacrificed 1 h after training and brains were collected to evaluate the immunoreactivity (IR) to GR, pSer232 and pSer246 by SDS-PAGE Western blot in DH and VH, and by immunohistochemistry in dorsal and ventral CA1, CA2, CA3 and dentate gyrus (DG) hippocampal regions. The conditioned freezing response increased in animals trained with 0.5 and 1.5 mA during training and extinction sessions. The degree of retention and CORT levels were directly related to the intensity of the foot-shock. Although total GR IR remained unaffected after conditioning, we observed a significant increase of pSer246 IR in the dorsal region of CA1 and in both dorsal and ventral DG. The only region in which pSer232 IR was significantly elevated was ventral CA3. Our results indicate that fear conditioning training is related to GR phosphorylation in specific subregions of the hippocampus, suggesting that its transcriptional activity for gene expression is favored in dorsal CA3, whereas its repressor activity for gene-silencing is increased in dorsal CA1 and in both dorsal and ventral DG.